Spermidine/spermine N1-acetyltransferase gene expression in A549 cells treated with pomegranate juice - Nik Abdul Malek, Nik Nurasyikin; Abdul Ghani, Radiah (2015)
Introduction: Intracellular polyamines have an important role in cell proliferation and death pathway. Targeting polyamine metabolic pathway is therefore a potential intervention in cancers. Either downregulation of polyamines synthesis or induction of polyamine catabolism both had been shown to cause depletion of intracellular polyamines. Objective: This study was aimed to investigate the expression of genes involved in polyamine catabolism, spermidine/spermine N1-acetyltransferase (SSAT)in human lung carcinoma A549 cells after treated with pomegranate juice. Methods: A549 cells were grown in DMEM supplemented with 10% (v/v) fetal bovine serum and 1% (v/v) penicillin-streptomycin. For experiment, cells were seeded at 1×104 cell/ml and grown for 48 hour prior to treatment. A549 cells were treated with 2% pomegranate juice for various exposure times between 0 to 48 hours. RNA was isolated using Trizol reagent and the purity of RNA was measured using NanoDrop spectrophotometer. The assays were analyzed using two steps quantitative real-time PCR by using Bio-Rad CFX96 Real-Time PCR Systems. The assays were normalized against two reference genes which are GAPDH and β-actin. Results: In this study, pomegranate juice did not induce the expression of SSAT. After 0, 6, 12, and 24 hour exposure, the expression of SSAT remains unchanged (p>0.05) compared to control. At 48 hour exposure, the expression of SSAT also remains unchanged although the relative normalized expression was lowered compared to control (p<0.05). Conclusion: To sum up, pomegranate juice had been shown to inhibit A549 cell lines proliferation although it did not induce the expression of SSAT. Therefore, it can be deduced that induction of SSAT is not involve in the death pathway in pomegranate juice treated human lung carcinoma A549 cell lines. Keywords: Polyamine catabolism, Pomegranate juice, Spermidine/spermine N1-acetyltransferase